Earth : an introduction to physical geology - Tarbuck, Edward J. (Prentice Hall, 2011)
An introduction to Geology -- Plate tectonics: a scientific revolution unfolds -- Matter and minerals -- Magma, igneous rocks, and intrusive activity -- Volcanoes and volcanic hazards -- Weathering and soil -- Sedimentary rocks -- Metamorphism and metamorphic rocks -- Geologic time -- Crustal deformation -- Earthquakes and earthquake hazards -- Earth's interior -- Divergent boundaries: origin and evolution of the Oceann Floor -- Convergent boundaries: origin of mountains -- Mass wasting: the work of gravity -- Running water -- Groundwater -- Glaciers and glaciation -- Deserts and winds -- Shorelines -- Global climate change -- Earth's evolution through geologic time -- Energy and mineral resources -- Planetary geology -- Metric and english units compared.